2,5-Diketopiperazines (DKPs): Promising Scaffolds for Anticancer Agents - Goher, Shaimaa S.; Abdrabo, Wessam S.; Veerakanellore, Giri Babu; Elgendy, Bahaa (Current Pharmaceutical Design, 2024)
2,5-Diketopiperazine (2,5-DKP) derivatives represent a family of secondary metabolites widely produced by bacteria, fungi, plants, animals, and marine organisms. Many natural products with DKP scaffolds exhibited various pharmacological activities such as antiviral, antifungal, antibacterial, and antitumor. 2,5-DKPs are recognized as privileged structures in medicinal chemistry, and compounds that incorporate the 2,5-DKP scaffold have been extensively investigated for their anticancer properties. This review is a thorough update on the anti-cancer activity of natural and synthesized 2,5-DKPs from 1997 to 2022. We have explored various aspects of 2,5-DKPs modifications and summarized their structure-activity relationships (SARs) to gain insight into their anticancer activities. We have also highlighted the novel approaches to enhance the specificity and pharmacokinetics of 2,5-DKP-based anticancer agents.
Keywords: anticancer activities